Software package for assessment of visual perception and anticipation ability in combat sport - Witte, K.; Emmermacher, P. (International Journal of Computer Science in Sport, 2011)
The purpose of this paper is to introduce equipment for estimation and training of anticipation performance in the combat sport karate. This equipment comprises a measuring station and a PC-software, which contains a database of videos and athletes, several tests and analysis routines and reports for the coach.